Rank, stress, and risk: A conjecture - Oded Stark; Julia Wlodarczyk (University of Bonn, Center for Development Research (ZEF), 2024)
A perception at the core of studies that consider the link between social rank and stress (typically measured by the so-called stress hormone cortisol) is that the link is direct. Examples of such studies are Bartolomucci (2007), Beery and Kaufer (2015), and Koolhaas et al. (2017). A recent and stark representation of this body of work is a study by Smith-Osborne et al. (2023), who state that "social hierarchies directly influence stress status" (Smith-Osborne et al. p. 1537, italics added). In the present paper, we reflect on this "direct" perspective. We conjecture that the link between social rank and stress involves an intervening variable: an indirect relationship arises when the loss of rank triggers a behavioral response in the form of risk taking aimed at regaining rank, and it is the engagement in risk-taking behavior that is the cause of an elevated level of cortisol. Smith-Osborne et al., as well as others whose papers are cited by Smith-Osborne et al. and who, like Creel (2001) and Avitsur et al. (2006), conducted comprehensive research on the association between rank (social standing) and stress, do not refer to risk taking at all. We present four strands of research that lend support to our conjecture: evidence that in response to losing rank, individuals are stressed; evidence that in response to losing rank, individuals resort to risk-taking behavior aimed at regaining their lost rank; evidence that there exists a link between engagement in risky activities or exposure to risk and elevated levels of cortisol; and an analytical perspective on incidence and intensity, namely a perspective that shows how the willingness to take risks responds to a change in rank, specifically, how a loss of rank triggers a greater willingness to take risks and how this trigger is stronger for individuals whose rank is higher.
Keywords: D01; D31; D81; D87; D91; I12; I14; 330; Social rank; Level of stress; Hormonal response; Risk-taking behavior; Elevated level of cortisol